Impact of work ethic commitment on job performance in Saudi Arabia - Alharazi, Kawther Naji (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at identify the ethics of work and its impact on job performance, A field study on employees and employees in Saudi organizations, the analytical descriptive approach was used by distributing its questionnaire and obtained (245) questionnaires, and several results were reached, the most important of which is: improving the functioning within organizations is not only done through the follow-up of regulations and instructions, but there is also a work ethic that represents an important and fundamental role in the life of societies, a manifestation of social control of individuals and has become a necessity of the administrative process in all Organizations, Therefore, laws and codes should be developed for the rules of work ethics and monitoring their application, raising awareness of the importance of work ethics and ensuring that workers are motivated to achieve good work, whether materially or morally.